Writing English in the Context of the Language Policy in Malaysia - Asmah Haji Omar (Journal of Modern Languages, 2017)
The paper considers the important role of English language to achieve the vision 2020 to be a contributor to the scientific and technological civilisation of the future. The author believes that, it cannot be achieved through Malay alone, but it has to be assigned by English, as the language known by most countries of the world.